Platinum-Based Drugs and DNA Interactions Studied by Single-Molecule and Bulk Measurements - Salerno, Domenico (Biophys J, 2016)
Platinum-containing molecules are widely used as anticancer drugs. These molecules exert cytotoxic effects by binding to DNA through various mechanisms. The binding between DNA and platinum-based drugs hinders the opening of DNA, and therefore, DNA duplication and transcription are severely hampered. Overall, impeding the above-mentioned important DNA mechanisms results in irreversible DNA damage and the induction of apoptosis. Several molecules, including multinuclear platinum compounds, belong to the family of platinum drugs, and there is a body of research devoted to developing more efficient and less toxic versions of these compounds. In this study, we combined different biophysical methods, including single-molecule assays (magnetic tweezers) and bulk experiments (ultraviolet absorption for thermal denaturation) to analyze the differential stability of double-stranded DNA in complex with either cisplatin or multinuclear platinum agents. Specifically, we analyzed how the binding of BBR3005 and BBR3464, two representative multinuclear platinum-based compounds, to DNA affects its stability as compared with cisplatin binding. Our results suggest that single-molecule approaches can provide insights into the drug-DNA interactions that underlie drug potency and provide information that is complementary to that generated from bulk analysis; thus, single-molecule approaches have the potential to facilitate the selection and design of optimized drug compounds. In particular, relevant differences in DNA stability at the single-molecule level are demonstrated by analyzing nanomechanically induced DNA denaturation. On the basis of the comparison between the single-molecule and bulk analyses, we suggest that transplatinated drugs are able to locally destabilize small portions of the DNA chain, whereas other regions are stabilized.